An Intelligent Speed Controller Design for Indirect Vector Controlled Induction Motor Drive System. (2016) - Shaija, P.J.; Daniel, Asha Elizabeth
Abstract: The aim of this paper is to present an Indirect vector control technique (Rotor- field Oriented) for a three phase Induction Motor drive using soft computing technique. Intelligent Speed Controller is being designed with Fuzzy Logic Controllers (FLC). Different Simulation experiments were carried out using MATLAB/SIMULINK to achieve at the best controller. The rules for the Fuzzy Controller were designed based on the dynamic behavior of the error signal. The performances of the proposed Fuzzy Logic Controller based Induction Motor drive are compared with that of the conventional PI controller based drive at different operating conditions.